Patient perceptions of nurses' cultural competence in public sector hospitals in Gauteng - Disebo R. Maboko; Sue Armstrong; Daleen Casteleijn (AOSIS, 2024)
Background: Healthcare institutions are increasingly receiving patients from diverse cultural backgrounds because of migration, rapid urbanisation, and easier access to healthcare. Because the satisfaction of these patients is linked to their perceptions of appropriate cultural care, understanding patient perspectives about cultural competence is imperative. Additionally, patient perceptions about nurses' cultural competence are largely unexplored in South Africa. Aim: This study explored how the concept of cultural competence is perceived by patients. Setting: Three public sector hospitals in Gauteng, one from each of the three different levels of public sector hospitals - district (level one), regional (level two), and academic (tertiary, level three). Methods: This study derives from the qualitative phase of a larger sequential exploratory mixed methods study. The study population was patients in public sector hospitals. A total of 21 interviews were conducted after purposive stratified sampling was done. Data analysis followed Tesch's eight steps of data analysis. Results: Patients in public sector hospitals in Gauteng believe consideration of culture is important in nursing. They identified the cultural needs they would like nurses to acknowledge, such as being asked about their food preferences and mentioned the need to evaluate nurses' level of cultural competence. Conclusion: Patient perceptions about cultural competence and their cultural needs can assist nurses in gauging how culturally competent they are and improving care to patients. Contribution: Patients' perceptions revealed that nurses must be competent to acknowledge their specific cultural needs such as food, language preferences, and religious practices.